Measuring Regional Islamic Bank Efficiency in Indonesia - Panorama, M (KnE Social Sciences, 2018)
Islamic banking comes to Indonesia which has strength that Indonesia famous with the largest Moslem in the world fairly late. Development of Islamic banks in Indonesia reflected through regional banks that come into sharia market. This study measures the size of the efficiency of regional banks using Data Envelopment Analisys. The DEA proceed by computer programe called Efficiency Measurement System which result that during the research period from 2005 to 2016, the efficiency of Sharia Regional Bank has been good. Highest Technical Efficiency, Scale Efficiency and Pure Technical Efficiency are Bank DKI Syariah, Bank Jabar Syariah and Bank Aceh Syariah. Keywords: Efficiency, Islamic Bank, Regional Bank, DEA, EMS